Elaboración de una guía de manualidades en artes plásticas con materiales de reciclaje para el área de cultura estética en la escuela Charles Darwin del cantón Saquisilí, de la comunidad de Yana Urco Grande en el año lectivo 2012-2013 - Cayambe López, Victoria Janeth (2013)
The present research has a goal; make a theorical and practical contribution to developed the children skill and creativity through a guide in Plastic Arts handbook in the beliefs area in the Charles Darwin School, Saquisilí canton in Yana Urco Grande Community during de school year 2012 – 2013, the main purpose is to reuse the materials such as paper, plastic, bottles card board, others and also conscious in the students’ parents and teachers the importance of reuse, create habits, customs and responsibility in each member around the community. The present research will take care especially in the scholar field trying to protect the environment, making an easy way to teachers and students with the guide; it can be used in all the scholar year because it is an excellent didactical material to develop the fine motor during the childhood.